Case Report: A case of Poirier–Bienvenu neurodevelopmental syndrome manifesting primarily as eyelid myoclonia - He, Yuanyuan; Deng, Qingqing; Chen, Chen; Liu, Zhanli; Weng, Lingwei (Frontiers in Pediatrics, 2025)
Variants in the CSNK2B gene are known to cause Poirier–Bienvenu neurodevelopmental syndrome (POBINDS). Since its first report in 2017, nearly 100 cases have been documented. Epileptic seizures and intellectual disabilities are core symptoms of POBINDS. While the CSNK2B genotype and phenotype exhibit increasing diversity, the genotype-phenotype correlation remains unclear. In this study, we identified a novel CSNK2B heterozygous mutation NM_001320.7:c.268A > C (p.Thr90Pro) in a child with Jeavons syndrome, classified as a likely pathogenic under ACMG guidelines. Computational analyses predicted that the change of c.268A > C (p. Thr90Pro) might have an impact on the stability of the protein. This pathogenic mutation enriches the spectrum of CSNK2B gene mutations and suggests that CSNK2B may be a causative gene for Jeavons syndrome.